2007
DOI: 10.1038/nmat1825
|View full text |Cite
|
Sign up to set email alerts
|

Polyprotein of GB1 is an ideal artificial elastomeric protein

Abstract: Naturally occurring elastomeric proteins function as molecular springs in their biological settings and show mechanical properties that underlie the elasticity of natural adhesives, cell adhesion proteins and muscle proteins. Constantly subject to repeated stretching-relaxation cycles, many elastomeric proteins demonstrate remarkable consistency and reliability in their mechanical performance. Such properties had hitherto been observed only in naturally evolved elastomeric proteins. Here we use single-molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
278
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 231 publications
(293 citation statements)
references
References 30 publications
11
278
0
4
Order By: Relevance
“…The number of domains in a polyprotein affects the measured mechanical stability, but this effect is small (36,37). Hence, our measured mechanical stability of Top7 using a heteropolyprotein does not differ from the value expected from a polyprotein (Top7) 8 . SMD Simulations.…”
Section: Methodsmentioning
confidence: 74%
See 3 more Smart Citations
“…The number of domains in a polyprotein affects the measured mechanical stability, but this effect is small (36,37). Hence, our measured mechanical stability of Top7 using a heteropolyprotein does not differ from the value expected from a polyprotein (Top7) 8 . SMD Simulations.…”
Section: Methodsmentioning
confidence: 74%
“…Our designed polyprotein chimera allows us to directly compare the mechanical stability of Top7 with that of GB1 (8,12). For the force-extension curves of the polyprotein chimera, we observed that the mechanical unfolding events of Top7 scattered among the GB1 unfolding events: the mechanical unfolding of Top7 can occur before any GB1 unfolding event or quite often after some of the GB1 domains have been unfolded.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…ELPs are promising scaffolding materials for certain tissue engineering applications [34]. Inspired by the natural elastomeric proteins, a small nonmechanical protein GB1 (the streptococcal B1 immunoglobulin-binding domain of protein G) was recently engineered into a polyprotein (GB1) 8 and was found to have excellent elastomeric properties [35], which could be a candidate material for tissue engineering scaffolds.…”
Section: Biomimetic Mechanical Propertiesmentioning
confidence: 99%